1987
DOI: 10.1080/00039896.1987.9935794
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Autopsy Populations for Previous Occupational Exposure to Asbestos

Abstract: A screening procedure to select, in autopsy populations, subjects having a major likelihood of previous occupational exposure to asbestos is described. To test our necropsy population we searched for pleural plaques (PPs); the optical count of both lung asbestos bodies (ABs) and uncoated mineral fibers (UMFs) at least 10 microns in length was recorded. In the adult autopsy population studied in the Turin area, the predictive value given by a positive test for large-size PPs (mostly bilateral) was about 55%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…There is also a fair correlation between the number of asbestos fibres in the lung parenchyma and the size of the plaques [5,12,13]. This agrees with the finding that the average and/or cumulative dust exposure is a significant determi nant for progression of pleural abnormalities [14], Since definite radiological criteria (as described under radiology below) will select the largest plaques, this will tend to select persons with a definite exposure.…”
Section: Size Of Plaques and Degree Of Exposuresupporting
confidence: 73%
“…There is also a fair correlation between the number of asbestos fibres in the lung parenchyma and the size of the plaques [5,12,13]. This agrees with the finding that the average and/or cumulative dust exposure is a significant determi nant for progression of pleural abnormalities [14], Since definite radiological criteria (as described under radiology below) will select the largest plaques, this will tend to select persons with a definite exposure.…”
Section: Size Of Plaques and Degree Of Exposuresupporting
confidence: 73%
“…The ABs were measured using about 100 mg (dehydrated tissue) of lung parenchyma without pleura or bronchi: the concentration (AB/gdw) was determined by optical count after membrane filtration of the material that was obtained by hypochlorite digestion. [8][9][10] Figure 1 shows a microphotograph of a preparation used to count ABs. A fragment of about 5 ml lung parenchyma was fixed and used for histological examination.…”
Section: Fibrosis and Asbestos Bodiesmentioning
confidence: 99%
“…In two of those autopsy series, there was an association between the degree of pleural plaques as estimated by their surface area at autopsy [Bianchi et al, 19881 or by their thickness on chest radiographs [Kishimoto et al, 19891 and the AB lung content. Mollo et al [1987] demonstrated that the prevalence of occupational exposure was positively correlated with the extent of pleural plaques at autopsy. By contrast, Wang et al [1988] found no relationship between the degree of pleural plaques at post mortem examination and duration of exposure or AB lung content.…”
Section: Pleural Plaque Score and Asbestos Exposurementioning
confidence: 95%
“…In epidemiological studies, a dose-response relationship has not been consistently established between asbestos exposure and pleural plaques. Moreoever, the relationship between the extent of pleural plaques and indices of exposure has been insufficiently documented [Mollo et al, 1987;Bianchi et al, 1988;Wang et al, 1988;Kishimoto et al, 19891. The purpose of the present study was to investigate the profiles of occupational asbestos exposure in hospital-based series of patients with bilateral pleural plaques and without any other radiological asbestos-related abnormalities. The relationship between a semiquantitative score of pleural plaques and the characteristics of asbestos exposure was also examined.…”
Section: Introductionmentioning
confidence: 99%